The fox's craft in Japanese religion and folklore : shapeshifters, transformations, and duplicities - Bathgate, Michael, 1967- (Routledge, 2004)
For more than a millennium, the fox has been a ubiquitous figure at the margins of the Japanese collective imagination. In the writings of the nobility and the motifs of popular literature, the fox is known as a shapeshifter, able to assume various forms in order to deceive others. Focusing on recurring themes of transformation and duplicity in folklore, theology, and court and village practice, The Fox's Craft explores the meanings and uses of shapeshifter fox imagery in Japanese history. Michael Bathgate finds that the shapeshifting powers of the fox make it a surprisingly fundamental symbol.
Keywords: Foxes -- Religious aspects.; Foxes -- Japan -- Folklore.; Inari.; Japan -- Religious life and customs.; Renards -- Aspect religieux.; Renards -- Japon -- Folklore.; SOCIAL SCIENCE -- Folklore & Mythology.; Foxes; Foxes -- Religious aspects; Inari; Japan; Electronic books.; Folklore